"Picturing" Xenophobia: Visual Framing of Masks During COVID-19 and Its Implications for Advocacy in Technical Communication. (January 2021) - Batova, Tatiana
This article reviews images of people of Asian descent wearing masks in popular press articles discussing mask shortages and argues that visual framing had the potential of fueling racial antagonism during the initial months of COVID-19's spread across the United States. Technical communicators need to include globalized perspectives in educational materials about masks as an advocacy strategy that can help communities and individuals to navigate the crisis situation and better protect themselves and those around them.